The Financial and Clinical Impact of an Electronic Health Record Integrated Pathway in Elective Colon Surgery - Austrian, Jonathan S.; Volpicelli, Frank; Jones, Simon; Bernstein, Mitchell A.; Padikkala, Jane; Bagheri, Ashley; Blecker, Saul (Applied Clinical Informatics, 2020)
Background Enhanced Recovery after Surgery (ERAS) pathways have been shown to reduce length of stay, but there have been limited evaluations of novel electronic health record (EHR)-based pathways. Compliance with ERAS in real-world settings has been problematic.Objective This article evaluates a novel ERAS electronic pathway (E-Pathway) activity integrated with the EHR for patients undergoing elective colorectal surgery.Methods We performed a retrospective cohort study of surgical patients age ≥ 18 years hospitalized from March 1, 2013 to August 31, 2016. The primary cohort consisted of patients admitted for elective colon surgery. We also studied a control group of patients undergoing other elective procedures. The E-Pathway was implemented on March 2, 2015. The primary outcome was variable costs per case. Secondary outcomes were observed to expected length of stay and 30-day readmissions.Results We included 823 (470 and 353 in the pre- and postintervention, respectively) colon surgery patients and 3,415 (1,819 and 1,596 in the pre- and postintervention) surgical control patients in the study. Among the colon surgery cohort, there was statistically significant (p = 0.040) decrease in costs of 1.28% (95% confidence interval [CI] 0.06–2.48%) per surgical encounter per month over the 18-month postintervention period, amounting to a total savings of $2,730 per patient at the 1-year postintervention period. The surgical control group had a nonsignificant (p = 0.231) decrease in monthly costs of 0.57% (95% CI 1.51 to – 0.37%) postintervention. For the 30-day readmission rates, there were no statistically significant changes in either cohort.Conclusion Our study is the first to report on the reduced costs after implementation of a novel sophisticated E-Pathway for ERAS. E-Pathways can be a powerful vehicle to support ERAS adoption.
Keywords: clinical pathways; clinical decision support; surgery; cost reduction and return on investment; evaluation